MENGENAL SISI LAIN POHON MAYANG BAGI KEHIDUPAN MANUSIA - Kaihena, Martha; Nusaly, Windy Natalia; Patty, Kristi Lenci; Salamena, Fuadiska; Manurung, Brian Saputra (Balobe: Jurnal Pengabdian Masyarakat, 2024)
The community service activity with the title "Knowing the Other Side of Mayang Tree for Human Life" is a form of concern for academics in the field of Biology for the spread of society and the development of home industry products that have an impact on improving the health and economy of the community. The transfer of information in the form of processing techniques, ways of utilisation, manufacturing procedures, and marketing techniques is carried out to educate the community in order to increase knowledge about the products and its biological processes. Scientifically, in the procedure of utilisation and processing of palm fruit (mayang), there are many science studies found in everyday life. In addition, indirectly, community students as recipients of information can apply it and become home industry producers. This is very helpful for the community in the utilisation of local wisdom in the area considering kolang kaling is a by-product of palm fruit (mayang) processing.